Senseless functions as a molecular switch for color photoreceptor differentiation in Drosophila. - Xie, B.; Charlton-Perkins, M.; McDonald, E.; Gebelein, B.; Cook, T. (Development, 2007)
A major question in development is how different specialized cell types arise from a common progenitor. In the adult Drosophila compound eye, color discrimination is achieved by UV-, blue- and green-sensitive photoreceptors (PRs). These different PR subsets arise from neuronal precursors called R7 and R8 cells. Recent studies have demonstrated that R7-based UV-sensitive PRs require the repression of R8-based blue/green-sensitive PR characteristics to properly develop. This repression is mediated by the transcription factor Prospero (Pros). Here, we report that Senseless (Sens), a Drosophila ortholog of the vertebrate Gfi1 transcription factor, plays an opposing role to Pros by both negatively regulating R7-based features and positively enforcing R8-based features during terminal differentiation. In addition, we demonstrate that Pros and Sens function together with the transcription factor Orthodenticle (Otd) to oppositely regulate R7 and R8 PR Rhodopsin gene expression in vitro. These data show that sens, previously shown to be essential for neuronal specification, also controls differentiation of specific neuronal subtypes in the retina. Interestingly, Pros has recently been shown to function as a tumor suppressor, whereas Gfi1 is a well-characterized oncogene. Thus, we propose that sens/pros antagonism is important for regulating many biological processes.